The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1074/jbc.m002134200
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase I Is Anchored on Axonemal Doublet Microtubules and Regulates Flagellar Dynein Phosphorylation and Activity

Abstract: Flagellar dynein activity is regulated by phosphorylation. One critical phosphoprotein substrate in Chlamydomonas is the 138-kDa intermediate chain (IC138) of the inner arm dyneins (Habermacher, G., and Sale, W. S. (1997) J. Cell Biol. 136, 167-176). In this study, several approaches were used to determine that casein kinase I (CKI) is physically anchored in the flagellar axoneme and regulates IC138 phosphorylation and dynein activity. First, using a videomicroscopic motility assay, selective CKI inhibitors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 60 publications
3
90
0
1
Order By: Relevance
“…In bovine and human sperm, mAKAP82 localized PKA, via its RII subunit, to the fibrous sheath (48), between the axoneme and the surrounding mitochondrion. In contrast, PKA of a single-celled flagellated alga, Chlamydomonas, is reported to be localized to the radial spokes of the flagellar structure, where it may be involved in regulating dynein ATPase (49). The location of PKA in giardial flagellar structure appears closer to that of mammalian sperm than to that of Chlamydomonas.…”
Section: Discussionmentioning
confidence: 75%
“…In bovine and human sperm, mAKAP82 localized PKA, via its RII subunit, to the fibrous sheath (48), between the axoneme and the surrounding mitochondrion. In contrast, PKA of a single-celled flagellated alga, Chlamydomonas, is reported to be localized to the radial spokes of the flagellar structure, where it may be involved in regulating dynein ATPase (49). The location of PKA in giardial flagellar structure appears closer to that of mammalian sperm than to that of Chlamydomonas.…”
Section: Discussionmentioning
confidence: 75%
“…3). Recent evidence has revealed that inner dynein arm subform I1 may play a role in controlling flagellar bending (23,31,(35)(36)(37)(38)(39). Therefore, we analyzed central apparatus orientation in axonemes isolated from the I1 defective strain ida1.…”
Section: Resultsmentioning
confidence: 99%
“…Inner-arm-dynein mutations of Chlamydomonas result in either complete or partial loss of coordinated beating. The 138 kD intermediate chain (IC138) is a protein that is associated with the inner-arm dyneins (Habermacher and Sale, 1997) and is actively phosphorylated by casein kinase 1 (Yang and Sale, 2000). Wirschell and colleagues state: 'The current model for regulation of I1-dynein is that chemical and/or mechanical signals from the central pair are transmitted through the radial spokes to affect IC138 phosphorylation on specific outer doublets (e.g.…”
Section: Dynein I1 and The Role Of The Cp-spoke Axismentioning
confidence: 99%